Evaluación de Mezclas de Arcillas de la Región de Guanajuato - Fuentes-Ramírez, Rosalba; Mejía Ordaz, Omar; de la Rosa Álvarez, Ma. Guadalupe; Caudillo, Bartolo; Guzmán Andrade, Juan José; Gallaga Ortega, Yolanda (Acta Universitaria, 2008)
Different clays of the state of Guanajuato were mixed and their properties were analyzed in order to select the best ceramic paste. The best mixture showed an excellent plastic molding and a linear contraction of 4,61% during the drying process. This process was analyzed using the Bigot curve at two different temperatures (60 and 80°C). The optimal firing temperature was 1030 °C. After the fi ring process, the pieces showed 12,3 % water absorption, 5,4 % contraction, a 91 HRB hardness and a compressive strength of 35 Kg/cm2.
Keywords: Array; Array; Array; Array